Crimped braided sleeves for soft, actuating arm in robotic abdominal surgery. Issue 4 (July 2015) - Elsayed, Yahya; Lekakou, Constantina; Ranzani, Tommaso; Cianchetti, Matteo; Morino, Mario; Arezzo, Alberto; Menciassi, Arianna; Geng, Tao; Saaj, CHAKRAVARTHINI M.
Abstract Background: This paper investigates different types of crimped, braided sleeve used for a soft arm for robotic abdominal surgery, with the sleeve required to contain balloon expansion in the pneumatically actuating arm while it follows the required bending, elongation and diameter reduction of the arm. Material and methods: Three types of crimped, braided sleeves from PET (BraidPET) or nylon (BraidGreyNylon and BraidNylon, with different monofilament diameters) were fabricated and tested including geometrical and microstructural characterisation of the crimp and braid, mechanical tests and medical scratching tests for organ damage of domestic pigs. Results: BraidPET caused some organ damage, sliding under normal force of 2-5 N; this was attributed to the high roughness of the braid pattern, the higher friction coefficient of polyethylene terephthalate (PET) compared to nylon, and the high frequency of the crimp peaks for this sleeve. No organ damage was observed for the BraidNylon, attributed to both the lower roughness of the braid pattern and the low friction coefficient of nylon. BraidNylon also required the lowest tensile force during its elongation to similar maximum strain as that of BraidPET, translating to low power requirements. Conclusion: BraidNylon is recommended for the crimped sleeve of the arm designed for robotic abdominal surgery.